A minireview on NHE1 inhibitors. A rediscovered hope in oncohematology - Mihaila, Romeo Gabriel (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2015)
BACKGROUND: Na(+)/H(+) exchanger-1 (NHE-1) is involved in pH regulation and is up-regulated in different malignancies. Activation of NHE-1 is one way for allowing cells to avoid intracellular acidification and protect them against apoptosis. Inhibitors of NHE-1 are able to decrease intracellular pH and induce apoptosis. Some statins can also act by partial inhibition of NHE-1. This review presents progress in understanding the mechanisms of action of these inhibitors, connections with certain genetic mutations and acquired treatment resistance, as well as new patents on them. METHODS: A MEDLINE search for original and review articles using key terms, Na(+)/H(+) exchanger, leukemia, cariporide, and amiloride. Recent patents with NHE-1 inhibitors published by United States Patent and Trademark Office are also presented. RESULTS AND CONCLUSIONS: Sorafenib is used for the treatment of acute myeloid leukemia patients carrying internal tandem duplication of fms-like tyrosine kinase 3 (FLT3-ITD) mutation. 5-(N, N-hexamethylene)-amiloride can increase the suppression of FLT3 signaling by sorafenib. NHE-1 inhibitors are able to increase the sensitivity of chronic myeloid leukemia cells to tyrosine kinase inhibitors, including through the inhibition of P-glycoprotein. NHE-1 inhibitors are promising adjuvant drugs for overcoming acquired resistance to treatment in various malignant hemopathies.
Keywords: Genes, abl; sodíko-vodíkový výměnný transportér 1; signální transdukce; upregulace; Leukemia, Myeloid, Acute; hemoxygenasa-1; statiny; Signal Transduction; proteiny přenášející kationty; tyrosinkinasa 3 podobná fms; Humans; lovastatin; inhibitory proteinkinas; Cation Transport Proteins; Up-Regulation; imatinib mesylát; Sulfones; lékové interakce; Sodium-Hydrogen Exchanger 1; Hydroxymethylglutaryl-CoA Reductase Inhibitors; P-glycoprotein; nádorová hypoxie; Imatinib Mesylate; mutace; Antineoplastic Agents; Niacinamide; amiloride; lidé; sorafenib; apoptosis; amilorid; Patents as Topic; osmolární koncentrace; Phenylurea Compounds; apoptóza; BCR/ABL; Drug Interactions; FLT3/ITD; leukemia; Sorafenib; geny abl; Protein Kinase Inhibitors; imatinib mesylate; patenty jako téma; isoprenylation; statins; chronická myeloidní leukemie; heme oxygenase-1; Osmolar Concentration; sulfony; niacinamid; Heme Oxygenase-1; Hydrogen-Ion Concentration; cariporide; nádorové buněčné linie; protinádorové látky; Guanidines; poškození DNA; fenylmočovinové sloučeniny; DNA Damage; fms-Like Tyrosine Kinase 3; Amiloride; intracellular pH; Cell Line, Tumor; Na+/H+ exchanger; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; guanidiny; Mutation; koncentrace vodíkových iontů; Sodium-Hydrogen Exchangers; akutní myeloidní leukemie; Apoptosis; Tumor Hypoxia; Na(+)-H(+) antiport